PEMANFAATAN PLATFORM GATHER TOWN SEBAGAI MEDIA KOMUNIKASI BEKERJA KARYAWAN (Studi Kasus Pada PT Sadulur Sinareng Raharja) - Mutiara Amelia (2024)
This research is motivated by developments in communication technology which have changed the way humans communicate. The development of communication technology presenting communication devices or known as new media that can be used as tools for communication. The use of communication media in this research is focused on communication media that carries the metaverse concept to answer the challenges of virtual communication more interesting and fun. This research was conducted on the Gather Town Platform at PT Sadulur Sinareng Raharja. This research aims to find how the utilization, supporting, and inhibiting factors of the Gather Town Platform as communication medium. The method used is qualitative with an explanatory case study approach. The result and discussion of this study are divided into three things. First, the utilization of Gather Town Platform is used as communication medium working for employees at PT Sadulur Sinareng Raharja in a form virtual office, the communication process requires specific communication devices, there are regulation or employee work culture, and there are five features that are most helpful, namely microphone and camera, sharescreen, pen maker, calendar, chat. Second, there are two support factors, namely unlimited space and time, and the advantage of Gather Town Platform because it carries the metaverse concept. Third, there are two inhibitory factors, namely the need for specific communication devices and high or wasteful quota consumption. Therefore, it can be concluded that the utilization of the Gather Town Platform at PT Sadulur Sinareng Raharja is related to the development of communication technology. Keywords: Computer Mediated Communication (CMC), Communication medium, Gather Town Platform